Culturally Responsive Professional Development Programs for Teacher Educators Using Community-Based Collaborative Learning: Lessons Learned from a Native American Community - Lydiah Nganga; John Kambutu (MDPI AG, 2024)
Earners from Native American communities in the U.S. experience unfamiliar curricula that are designed and implemented by educators from the dominant culture who are often unprepared to meet the needs of diverse leaners. Consequently, teacher education programs have a responsibility to equipe preservice teachers with knowledge and skills essential to integrating culturally relevant contents. Therefore, this collaborative autoethnography conducted as a teacher-educator professional development program, explored the perspectives of Native Peoples on preferred pedagogical approaches for Indigenous learners. Data were collected through autobiographical notes, written reflections, focus groups, interactive activities with study participants, and structured interviews. A thematic analysis resulted in two findings, that is, importance of contextually appropriate curriculum and the value of community-based collaborative learning professional development activities in supporting authentic culturally responsive lessons for teacher educators. Among other recommendations, the data support the enactment of teacher education programs that support intentional culturally collaborative Community-Based Professional Development activities between educators and Indigenous Peoples.